Knowledge of nutrition facts on food labels and their impact on food choices on consumers - Elexson, Nillian; EASTERINA EMPINA, EDWIN; Mastura, Sani; Sharifah N., W. A.; Manju, S.; Bryan, V.L.Q.; Clement, E.; Vaneesa, T.; Aazhaiqal, A. R.; Patricia, G. (Rynnye Lyan Resources, 2025)
Food labels are mandatory on all food products since they contain nutrition information to help consumers make informed dietary decisions. Although food labels are widely available, many consumers struggle to fully understand the information they provide. The primary goal of this study is to evaluate how knowledge of nutrition facts influences the food choices of residents in Batu Pahat, Johor. A descriptive research design was done, involving three hundred (n=300) consumers and three hundred (n=300) local food products. A structured questionnaire was distributed across four major supermarkets and hypermarkets. The questionnaire assessed awareness, attitudes, and use of food labels, while the compliance of food labels for local products has been evaluated using the Food Regulation 1985 guideline. The frequency and percentage of the data have been calculated using SPSS software. Findings revealed that 77.3% of consumers were aware of food labels, and 78.0% referred to ingredient lists when selecting products. However, only 20.7% understood complete food label information. Most local food products complied with major labeling requirements, although some products lacked allergen and distributor information. In conclusion, while consumers generally believe in and rely on food labels, there is a need to improve their understanding of the full range of nutritional information. Strengthening labeling policies and improving consumer education can support healthier food choices.